2012
DOI: 10.2105/ajph.2011.300396
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Exposure to Intimate Partner Violence and the Risk of Undernutrition Among Children Younger Than 5 Years in Bangladesh

Abstract: The association between maternal exposure to physical or sexual IPV and child underweight and stunting suggests that partner violence plays a significant role in compromising child health by impairing child nutrition. Our findings reinforce the evidence that improving child nutrition is an additional reason to strengthen efforts to protect women from physical and sexual IPV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
54
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 41 publications
4
54
0
1
Order By: Relevance
“…Analyzing data from Bangladesh Demographic and Health Surveys (BDHS) 2007, Rahman et al (2012) found that 29% of the women experienced IPV in the year preceding the survey, which was associated with increased risk of stunting and underweight among children. Although IPV is widespread, very little research has been conducted on understanding the factors associated with IPV tolerance in Bangladesh.…”
Section: Cultural Contextmentioning
confidence: 99%
“…Analyzing data from Bangladesh Demographic and Health Surveys (BDHS) 2007, Rahman et al (2012) found that 29% of the women experienced IPV in the year preceding the survey, which was associated with increased risk of stunting and underweight among children. Although IPV is widespread, very little research has been conducted on understanding the factors associated with IPV tolerance in Bangladesh.…”
Section: Cultural Contextmentioning
confidence: 99%
“…Most studies focused on the relationship between physical and sexual IPV and health outcomes [23]. Little is known about the link between emotional IPV and partner controlling behavior with utilization of maternal health care services.…”
Section: Introductionmentioning
confidence: 99%
“…Boynton (2010) found an association between child obesity and maternal BMI, smoking during pregnancy, marital status as well as child factors such as television watching, birth weight and bottle-feeding. In another study, stunting and underweight were associated with high wealth score and recent child illness (Rahman et al, 2012). Wasting was associated with, maternal decision-making and male gender (Rahman et al, 2012).…”
Section: Resultsmentioning
confidence: 92%
“…In another study, stunting and underweight were associated with high wealth score and recent child illness (Rahman et al, 2012). Wasting was associated with, maternal decision-making and male gender (Rahman et al, 2012). Higher education and decision-making among mothers were associated with higher WHZ, HAZ, and WAZ scores implying that these children were growing normally or tended towards obesity .…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation